OMALIZUMAB IN SEVERE ATOPIC DERMATITIS - Luz, Sofia (2011)
We present the cases of two young females with severe atopic dermatitis, treated with anti-histamines, topical corticosteroids, high-dose systemic corticosteroids bursts and/or oral cyclosporine, without significant improvement and worsening with tapering of corticosteroids and/or cyclosporine. Several therapeutical adjustments were made without success before starting treatment with subcutaneous omalizumab. The clinical evolution of these patients undergoing treatment with omalizumab is described and its role in the treatment of atopic dermatitis is discussed.